Performance Comparison and Lysine Requirements of Seven Commercial Brown Egg Layer Strains During Phase Two - Gunawardana, P.; Roland, D.A.; Bryant, M.M. (International Journal of Poultry Science, 2008)
This study was a 3 x 7 factorial arrangement with 3 lysine levels (0.828, 0.747 and 0.680) and 7 commercial brown egg layer strains. The objective of this experiment was to determine the effect of increasing dietary lysine on performance, egg composition, egg solids, egg quality and profits in 7 commercial brown egg l ayer strains and to determine the lysine requirement during phase 2 (from 39-52 week of age). This experiment lasted 14 weeks. Seven strains of hens (n = 240 of each strain) at 39 week of age were randomly divided into 21 treatments (8 replicates of 10 birds/treatment). The results showed that there were no interactions between lysine and strain on any parameter. Lysine had significant effects on feed consumption, egg production, egg mass, feed conversion, egg weight, egg shell components, percent yolk and whole egg solids, albumen and yolk weight, egg specific gravity, yolk color and haugh units. There were significant strain effects on feed consumption, egg mass, feed conversion, egg weight, albumen and yolk components, whole egg solids, albumen and shell weight, egg specific gravity, body weight, shell color and haugh unit. Strain 1 had the best overall performance. All strains were laying 89.5-92.5% at 52 weeks of age. Average egg weight (39-52 week) was 63 g, varying from 61.5-63.6 g between strains. Average feed intake was 112.1 g/hen/day varying from 108-114 g/hen/day between strains. Average egg weight of hens fed diets containing the highest lysine level was 3.38 g heavier than hens fed the diets containing the lowest lysine level. Increasing dietary lysine from 0.680-0.828% significantly improved feed conversion from 2.03-1.91 g feed/g egg and increased egg mass from 54.0-59.30 g/hen/day. Average lysine intake of hens fed 0.828% level was 939 mg/hen/day varying from 907-964 mg/hen/day between strains. Because egg and ingredient prices often change, there can be no fixed dietary lysine level for optimal profits.